New quasioptical receiving system for electron cyclotron emission diagnostics in Uragan-3M stellarator - Pavlichenko, R.O. (Вопросы атомной науки и техники, 2014)
A new electron cyclotron emission antenna was designed to be installed outside of Uragan-3M vacuum tank. The system will be utilizing different diagnostic port to minimize the length of the output microwave beam. Its design is based on Gaussian beam optics and consists of two plane and two concave mirrors. The concave mirror surfaces are defined using the concept of elliptical surface, where the origin of emission and outside detection antenna coincide with foci of ellipsoid. The new electron cyclotron emission antenna will be installed for a 2015 experiment to measure the electron temperature profile and its fluctuations. This paper reports the general design of the new quasi-optical antenna system.